Criteria required in Venezuelan dental journals for the publication of the extraoral photographs in case reports - Avendaño, Airin (2022)
Objective. To describe the criteria required in Venezuelan dental journals for the publication of extraoral clinical photography in clinical cases published in the period 2010-2021. Methods. Research with a quantitative approach, descriptive scope, and cross-sectional design. Scientific articles that included extraoral clinical photographs published in Venezuelan dental journals between 2010 and 2021 were analyzed. Results. There was a need from the publisher in the strategies of preservation of the patient’s identity, and to the use of informed consent for the publication of photographs. extraoral clinics of clinical cases. Conclusions. The Acta Odontológica journal makes greater use of informed consent, in addition to using masking and anonymity as a method of identity preservation in its publications.